Postnatal development of the relaxin-3 innervation of the rat medial septum - Ros-Bernal, Francisco; Gil-Miravet, Isis; Lucerón, Jorge; Navarro-Sánchez, Mónica; Castillo-Gómez, Esther; Gundlach, Andrew L.; Olucha-Bordonau, Francisco E. (Frontiers in Neuroscience, 2023)
The septal area provides a rich innervation to the hippocampus regulating hippocampal excitability to different behavioral states and modulating theta rhythmogenesis. However, little is known about the neurodevelopmental consequences of its alterations during postnatal development. The activity of the septohippocampal system is driven and/or modulated by ascending inputs, including those arising from the nucleus incertus (NI), many of which contain the neuropeptide, relaxin-3 (RLN3). In this study we examined the ontogeny of the RLN3 innervation of the septal area by analyzing brains from postnatal day (P) 10, 13, 15, 17, 20 and 30, and mature adult rats. Up until P13–15 there were only scattered fibers in the septal area, but a dense plexus had appeared by P17 that was extended and consolidated throughout the septal complex by P20. There was a decrease in the level of colocalization of RLN3 and synaptophysin between P15 and P20 that was reversed between P20 and adulthood. Biotinylated 3-kD dextran amine injections into the septum, revealed retrograde labeling present in the brainstem at P10-P13, but a decrease in anterograde fibers in the NI between P10–20. Simultaneously, a differentiation process began during P10–17, resulting in fewer NI neurons double-labeled for serotonin and RLN3. The onset of the RLN3 innervation of the septum complex between P17–20 is correlated with the onset of hippocampal theta rhythm and several learning processes associated with hippocampal function. Together, these data highlight the relevance and need for further analysis of this stage for normal and pathological septohippocampal development.